Enough is enough building a sustainable economy in a world of finite resources - Dietz, Rob (Berrett-Koehler, 2013)
We're overusing the earth's finite resources, and yet excessive consumption is failing to improve our lives. In Enough Is Enough, Rob Dietz and Dan O'Neill lay out a visionary but realistic alternative to the perpetual pursuit of economic growth--an economy where the goal is not more but enough. They explore specific strategies to conserve natural resources, stabilize population, reduce inequality, fix the financial system, create jobs, and more--all with the aim of maximizing long-term well-being instead of short-term profits. Filled with fresh ideas and surprising optimism, Enough Is Enough is the primer for achieving genuine prosperity and a hopeful future for all.